Red sings from treetops eaudiobook - Sidman, Joyce (Recorded Books Inc., 2011)
In spring, Red sings from treetops: cheer-cheer-cheer, each note dropping like a cherry into my ear. Sleepy Yellow sticks to summer. Yet ocean Blue stays cool and alive. Green fades in fall, turns to dust, and no longer keeps Brown at bay. In winter, Pink blossoms on chilled cheeks. And Black echoes through the still of winter's night. But spring comes again, and Red returns-flitting and fluttering, bright as a Cardinal bird. Winner of a Caldecott Honor, this delightful book of free verse poems by celebrated poet Joyce Sidman is "a charming inspiration to notice colors and correlate emotions" (Kirkus Reviews). With each verse of Barbara Caruso's spellbinding narration, children and adults alike will appreciate the colors of the seasons. ". as the title implies, the colors that surprise on every page do sing."-Booklist, starred review